Influence of sustainable logistics practices on logistics transport performance of transport service providers in Malaysia - Kumar, Kavigtha Mohan (2017)
Sustainable logistics practices is an extension of sustainable supply chain management (SSCM) which specifically serves the logistics and transportation sector. The application of sustainable logistics is a key enabler for transport service providers’ competitive advantage. The primary objective of this thesis is to determine the extent to which sustainable logistics practices influence logistics transport performance. The study also explores the effects of supplier support between sustainable logistics practices and logistics transport performance. A questionnaire survey was employed involving 194 transport users from food and non food industries sensitive to sustainable issues, namely the food, chemical, pharmaceutical, and medical industries. These industries were categorized as food and non-food industries. Data were analyzed using Smart PLS Software. The response rate for the research was within the range deemed acceptable in the Malaysian context. The results indicate that logistics service execution, pricing practice and labor practice have relationship on logistics transport performance. In the transportation context, it was found that safety and security are suitable constructs under social sustainability. Practices related to safety and security are embedded within the service offerings practices. Next, pricing practice and labor practice were found significant with supplier support. Supplier support and logistics transport performance were also found to have a strong relationship. This explains the relationship strength between the transport user and transport service providers. Furthermore, the analysis shows that supplier support plays strong mediating role between pricing practice / labor practice and logistic transport performance. Overall the results generate novel insights concerning transport users preferences on sustainable practices and their opinion on delivery services offered by transport service provider.